Pengaruh Citra Perusahaan, Asal Negara, dan Keragaman Produk Terhadap Minat Beli Ulang McDonald’s Sedati Sidoarjo - Misbachul Munir; Saiyidatun Nisa’ (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Globalization not only has an impact on technology but also on other aspects. With globalization, various types of food from around the world can be enjoyed without having to come to their country of origin. Besides that at this time the food is also served quickly. Several fast food restaurants have been established and reach the international market. One of them is McDonald's. This fast food company has stores in almost all countries in the world. But McDonald’s also has to compete with other fast-food restaurants. Not only to find new consumers but also to increase consumers' desire to repurchase McDonald's products. Therefore, management needs to increase the supporting factors of McDonald's repurchase interest such as company image, country of origin, and product diversity. This study was conducted to determine the effect of company image, country of origin, and product diversity on the formation of McDonald's repurchase interest. The population of this research is McDonalds Sedati Sidoarjo consumers who have bought McDonald's Sedati Sidoarjo products more than twice. The study used 200 samples with probability sampling technique. Data analysis using SPSS with multiple linear regression technique. The results showed that the company's image had a significant effect on the repurchase intention of McDonald's Sedati Sidoarjo. Furthermore, country of origin has also been shown to have a significant influence on the repurchase intention. The formation of repurchase interest has also been shown to have a significant effect on product diversity. Company image, country of origin, and product diversity have been shown to have a significant influence on the repurchase intention